LEVELS OF DEPRESSION AMONG ADOLESCENT GIRLS WITH EARLY MARRIAGE - Lia Yuliana Rachman; Efri Widianti; Anita Setyawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Early marriage encourages various problems for young women. The problems would be affecting their psychological conditions including depression. This study aimed to describe the depression in adolescent girls with early marriage in Babakan Ciparay District, Bandung City. This study was conducted using the descriptive explorative method, with a cross-sectional approach. Samples were selected using the total sampling technique, in which 76 young women aged 16-19 years involved in this study. This study used an instrument from the Indonesian version of the Beck Depression Inventory-II (BDI-II) questionnaire with validity values at 0.361-0.773 and the value of Cronbach's alpha is 0.898, and several additional questions related to the problems experienced by girls who married early. The data were analyzed using descriptive statistical analysis techniques for quantitative data and content analysis for interview data. This study was held in the range of April - May 2019. The results showed that 68.4% of respondents were at a minimum level of depression or did not experience depression, 11.8% had mild depression, 10.5% had moderate depression and 9.2% had severe depression. It can be concluded that the young women did not experience depression, because most respondents married with own desires, lived separately from their parents-in-law and did not experience domestic violence. However, there were still some respondents who are depressed or have the potential to experience depression due to economic problem, problems with in-laws, problems with their husbands and problems related to family relationships. Therefore, there is a need for education about stress management and counseling program to improve the mental health of girls who married early.Keywords: adolescent girl, depression, early marriage